Isomeric Cd(NH4)2(PO3F)2·2H2O: Solution concentration-driven elimination of antiparallel dipole-dipole interaction generating an SHG β phase. (February 2023) - Yang, Xin-Rui; Liu, Xin; Deng, Xue-Bin; Chen, Ling; Wu, Li-Ming
Abstract: As the core of all-solid-state lasers, the second harmonic generation (SHG) inorganic crystals exclusively require a noncentrosymmetric (NCS) structure. However, the vast majority of the known inorganic compounds, approximately 79%, are centrosymmetric (CS). Herein, we report a unique concentration-driven isomerization of the β and α phases of Cd(NH4 )2 (PO3 F)2 ·2H2 O, β -CdNPF ( Cmc 21, NCS) and α -CdNPF ( P 21 / n, CS). The NCS β -CdNPF is generated at a higher mother solution concentration ( β vs. α phase: 0.20 vs. 0.15 M), which allows the [CdO6 ] octahedron accommodate higher number of the [PO3 F] ligand with a weak crystal field (CN = 4 vs. 3), leading to a dipole moment reduction (1.06 D vs. 1.60 D) that eventually eliminates the unwanted symmetric center trap induced by the antiparallel dipole-dipole interactions between the [CdO6 ] octahedra in the CS α -CdNPF. Interestingly, such a slight trans - vs. facial -[CdO6 ] geometry difference in the β and α phases, also makes the Cd-fluorescence red-shift slightly (437 vs. 431 nm) and narrows E g slimly (cal.: 4.01 vs. 4.05 eV). More interestingly, β -CdNPF exhibits excellent NLO properties (relatively strong phase matching SHG: 0.78 × KDP at 1064 nm; deep ultraviolet (DUV) transparent ( λ cutoff  < 200 nm); high laser induced damage threshold: 1.48 × KDP), indicating a promising DUV NLO application potential. Graphical abstract: The dipole moment reduction of the [CdO6 ] building unit eliminates the unwanted symmetric center trap that is induced by the antiparallel dipole-dipole interactions between the [CdO6 ] octahedra as happening in α -CdNPF, generating β -CdNPF that exhibits a strong SHG intensity (0.78 × KDP at 1064 nm). Image 1 Highlights: The first SHG active Cd-containing monofluorophosphate, β -CdNPF (SHG = 0.78 × KDP; LIDT = 1.48 × KDP) is reported. For inorganic isomers, we report for the first time the concentration-driven isomerization. Building unit [CdO6 ] having more [PO3 F] 2- ligands exhibits less distortion and polarization, which eliminates the centrosymmetric trap. Such a slight local coordination geometry difference also makes the Cd-fluorescence red-shift and narrows the  E g .